A dual inhibitor of matrix metalloproteinases and a disintegrin and metalloproteinases, [18F]FB-ML5, as a molecular probe for non-invasive MMP/ADAM-targeted imaging. Issue 1 (1st January 2015) - Matusiak, Nathalie; Castelli, Riccardo; Tuin, Adriaan W.; Overkleeft, Herman S.; Wisastra, Rosalina; Dekker, Frank J.; Prély, Laurette M.; Bischoff, Rainer P.M.; van Waarde, Aren; Dierckx, Rudi A.J.O.; Elsinga, Philip H.
Graphical abstract: Abstract: Background: Numerous clinical studies have shown a correlation between increased matrix metalloproteinase (MMP)/a disintegrin and metalloproteinase (ADAM) activity and poor outcome of cancer. Various MMP inhibitors (MMPIs) have been developed for therapeutic purposes in oncology. In addition, molecular imaging of MMP/ADAM levels in vivo would allow the diagnosis of tumors. We selected the dual inhibitor of MMPs and ADAMs, ML5, which is a hydroxamate-based inhibitor with affinities for many MMPs and ADAMs. ML5 was radiolabelled with 18 F and the newly obtained radiolabelled inhibitor was evaluated in vitro and in vivo. Materials and methods: ML5 was radiolabelled by direct acylation with N -succinimidyl-4-[ 18 F]fluorobenzoate ([ 18 F]SFB) for PET (positron emission tomography). The resulting radiotracer [ 18 F]FB-ML5 was evaluated in vitro in human bronchial epithelium 16HBE cells and breast cancer MCF-7 cells. The non-radioactive probe FB-ML5 and native ML5 were tested in a fluorogenic inhibition assay against MMP-2, -9, -12 and ADAM-17. The in vivo kinetics of [ 18 F]FB-ML5 were examined in a HT1080 tumor-bearing mouse model. Specificity of probe binding was examined by co-injection of 0 or 2.5 mg/kg ML5. Results: ML5 and FB-ML5 showed high affinity for MMP-2, -9, -12 and ADAM-17; indeed IC50 values were respectively 7.4 ± 2.0, 19.5 ± 2.8, 2.0 ± 0.2 and 5.7 ± 2.2 nM and 12.5 ± 3.1, 31.5 ± 13.7, 138.0 ± 10.9 and 24.7 ± 2.8 nM. Radiochemical yield of HPLC-purified [ 18 F]FB-ML5 was 13–16% (corrected for decay). Cellular binding of [ 18 F]FB-ML5 was reduced by 36.6% and 27.5% in MCF-7 and 16HBE cells, respectively, after co-incubation with 10 μM of ML5. In microPET scans, HT1080 tumors exhibited a low and homogeneous uptake of the tracer. Tumors of mice injected with [ 18 F]FB-ML5 showed a SUVmean of 0.145 ± 0.064 ( n  = 6) which decreased to 0.041 ± 0.027 ( n  = 6) after target blocking ( p  < 0.05). Ex vivo biodistribution showed a rapid excretion through the kidneys and the liver. Metabolite assays indicated that the parent tracer represented 23.2 ± 7.3% ( n  = 2) of total radioactivity in plasma, at 90 min post injection (p.i.). Conclusion: The nanomolar affinity MMP/ADAM inhibitor ML5 was successfully labelled with 18 F. [ 18 F]FB-ML5 demonstrated rather low binding in ADAM-17 overexpressing cell lines. [ 18 F]FB-ML5 uptake showed significant reduction in the HT1080 tumor in vivo after co-injection of ML5. [ 18 F]FB-ML5 may be suitable for the visualization/quantification of diseases overexpressing simultaneously MMPs and ADAMs.